Current ESWL practice and outcomes in the UK: A multicentre snapshot. (July 2017) - Doherty, R; Manley, K; Gordon, S; Irving, S; Kumar, S; Masood, J; Philip, J; Bultitude, M; Wiseman, OJ
Objectives: The objective of this article is to investigate the current clinical practice and outcomes of extracorporeal shock wave lithotripsy (SWL) in the United Kingdom. Patients and methods: Patient demographics, stone characteristics and SWL protocols were collected prospectively for 30 consecutive new patient referrals at each of seven contributing UK institutions performing SWL. Final outcomes in terms of stone-free rates (SFRs), and complications were recorded. Results: Completed demographic data were available for 204 patients. Treatment protocols varied between centres. Mean patient age was 51 years. Over 70% of stones treated measured between 5 and 10 mm, and one-third were in the ureter, with two-thirds in the kidney, where the majority (31% overall) were in the lower pole. The overall cumulative SFR was 50.3% (range 33–70% between centres). SWL was notably more effective for ureteric stones (SFR 59.3% overall) than for renal calculi (SFR 45.6% overall). Complications were noted in six patients. Conclusion: This study provides a valuable snapshot of real-life clinical practice and demonstrates considerable variability in the application of SWL in the UK. The results support existing data which suggest that SWL is a safe and well tolerated treatment modality; however, overall SFRs were low.